Inositol Hexakisphosphate (InsP₆) Induces Apoptosis via Caspase-Dependent Pathways: Molecular Docking Insights - Ferry Sandra; Dewi Ranggaini; Johni Halim; Alfred Pakpahan; Visi Endah Pratitis; Kyung Hoon Lee (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Inositol hexakisphosphate (InsP₆) exhibits anticancer activity, especially by inducing intrinsic and extrinsic apoptotic pathways. However, there is still no molecular docking evidence that directly examines InsP₆ interactions with either upstream or downstream apoptotic regulators. Therefore, the current study was conducted to investigate the molecular docking of InsP₆ to caspases as upstream/downstream apoptotic regulators.METHODS: Ligands including InsP₆, InsP₅, InsP₄, histone deacetylase inhibitor, and caspase inhibitors were retrieved from PubChem, while target proteins (histone, caspase-8, caspase-2, and caspase-3) were obtained from the Protein Data Bank. Ligand toxicity was predicted using ProTox-3.0, and physicochemical properties were analyzed with SwissADME. Ligand structures were energy-minimized using PyRx with the Universal Force Field, while proteins were prepared by removing water molecules and non-essential heteroatoms in BIOVIA Discovery Studio. Molecular docking was conducted using CB-Dock 2.0, with binding poses selected based on the lowest Vina score, and ligand–protein interactions were visualized in Discovery Studio.RESULTS: Molecular docking results showed that InsP₆ bound strongly to histone, caspase-8, caspase-2, and caspase-3 with affinities comparable to reference inhibitors, forming multiple hydrogen bonds with key active-site residues. InsP₆, InsP₅, and InsP₄ exhibited several similar binding sites to caspase-3, with only minor differences in binding affinity.CONCLUSION: InsP₆ shows strong binding to histone, caspase-8, caspase-2, and caspase-3 based on in silico results, supporting its role in inducing both extrinsic and intrinsic apoptotic pathways. Taken together, InsP₆ could be a potential inducer of apoptosis in cancer cells.KEYWORDS: cancer, apoptosis, InsP₆, InsP₅, InsP₄, caspase, in silico, molecular docking